Surface morphology and optical properties of Ca and Mn doped TiO2 nano-structured thin films - Caligulu, Ugur; Darcan, Nida; Kejanli, Haluk (Elsevier - Division Reed Elsevier India Pvt Ltd, 2021)
This study was conducted to investigate the impact of Calcium (Ca) and Manganese (Mn) dopants on the optical and surface properties of Titanium dioxide (TiO2) nanomaterial. Ca and Mn doped TiO2 thin films were fabricated by sol-gel spin-coating method. By keeping the doping ratio of Ca constant, Mn was doped at the ratios of 1, 3, and 5%. The morphological, structural and optical properties of the fabricated samples were taken by Atomic Force Microscope (AFM), Scanning Electron Microscope (SEM), Energy Dispersive X-Ray Analysis (EDX), X-Ray Diffraction Method (XRD) and UV-VIS spectroscopy. AFM and SEM analysis revealed that the morphological properties of TiO2 changed depending on the increase in doping ratio of Mn. XRD values obtained from the samples showed that the increases of crystallite size with manganese ions doping into the TiO2 the optical band gap of the samples increased with Ca and Mn dopants. As a result of the investigations, it was determined that Mn doping has significant effects on the morphological and optical properties of TiO2 films and the produced samples can be used in transparent conductive electrode applications, optoelectronic devices, and sensor production. (C) 2021 Karabuk University. Publishing services by Elsevier B.V.
Keywords: TiO2; Ca-Mn; Thin film; Sol gel-spin coating; Nanomaterials